Research on the Correlation of Safety Risk of Railway Bridge Construction Based on Meta-Analysis - Zhi Shan; Yuling Liang; Zhiwu Yu; Huihua Chen (Applied Sciences, 2024)
China has emerged as a prominent global player in the field of railways, with numerous railway construction projects spanning across diverse locations. Railway bridges, as a crucial component of railway construction, warrant significant attention. Meta-analysis, a statistical method that systematically synthesizes research findings, has been utilized to summarize and compare the results of safety risk management studies pertaining to railway bridge construction in China. By integrating social network analysis and evidence-based assessment of the literature, this study explores the interrelationships among risk factors. Within a specific railway bridge construction project, various safety risk factors may originate from common sources, including environmental factors, material and equipment factors, technical factors, management factors, personnel factors, and bridge-specific factors. Notably, there exists coupling among these security risk factors, whereby the presence or occurrence of one factor can influence the probability or severity of consequences associated with other factors. The results reveal that safety risk factors in railway bridge construction accumulate and propagate, thereby impacting the efficacy of safety risk management. Moreover, these factors are significantly influenced by the complexities inherent in the geo-meteorological and social-technical systems. This finding provides valuable insights for innovations in security risk management practices and offers suggestions for future innovation pathways.